2020
DOI: 10.1007/s00432-020-03217-7
|View full text |Cite
|
Sign up to set email alerts
|

Treatment discontinuation and re-initiation of anti-PD-(L)1 agents in metastatic cancers

Abstract: Introduction Immune checkpoint inhibitors (ICIs) are approved in multiple indications for cancer care. Most of the clinical trials have not questioned shorter than until disease progression approaches. In this study, we present results from a cohort of multiple advanced cancers treated with restricted anti-PD-(L)1 therapy. Methods All patients with advanced cancers treated with anti-PD-(L)1 therapy outside clinical trials at Oulu University Hospital 2014-19 were retrospectively identified from pharmacy records… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…More recently, in a study by Warner et al, only five (15%) of 34 patients responded to anti-PD-1 re-treatment [ 8 ]. Other reports included only 3–8 patients [ 2 , 9 , 12 , 21 , 29 , 30 ]. Overall, 47% ( n = 9) of our patients responded to re-treatment with anti–PD-1 therapy.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, in a study by Warner et al, only five (15%) of 34 patients responded to anti-PD-1 re-treatment [ 8 ]. Other reports included only 3–8 patients [ 2 , 9 , 12 , 21 , 29 , 30 ]. Overall, 47% ( n = 9) of our patients responded to re-treatment with anti–PD-1 therapy.…”
Section: Discussionmentioning
confidence: 99%
“…An elective treatment discontinuation before progression of 10%-30% was reported in real-world analyses in other cancer types. [9][10][11] We observed favorable survival outcomes after drug discontinuation, especially in patients with CR. Although the follow-up data were immature, half of all patients and two-thirds of patients with CR were free from treatment and progression for more than 2 years.…”
Section: Discussionmentioning
confidence: 78%
“…The protocol and clinical setting of the trial can explain the difference in results versus our observations. An elective treatment discontinuation before progression of 10%–30% was reported in real‐world analyses in other cancer types 9–11 …”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, there is no clear evidence on how long treatment should continue 16,17 . Other studies have reported that the drug was effective once it was discontinued and readministered when it recurred 18,19 . If the tumor completely disappears as in the present case, then it may be possible to administer pembrolizumab for a certain period, discontinue it, and if cancer recurs, re‐challenge it.…”
Section: Discussionmentioning
confidence: 81%